Gemstone of analysis: Significance of interpretation of dreams in analytic process - Blazhina, Iryna (Psychosomatic Medicine and General Practice, 2021)
Background. Dreams are able to reflect the patients’ experience as well as testify one or another stage of mental illness. However, in the scientific world, not enough attention is given to the analysis of dreams. The purpose of this study is to review the scientific literature regarding the features, functions, symbolic content and representations of dreams. Design: systematic review. Subject of study. The review of scientific publications was conducted on neurophysiology of dreams, basic concepts of analysis, meaning, functions of dreams and psychoanalytic interpretation techniques. Results. At present, it is believed that dreams have protective and adaptive functions and contribute to the formation of long-term memory and information processing of emotionally charged experiences; At the same time, dreams are the result of the creative process. On the one hand, dreaming satisfies the need of the Ego in a dream because it protects the state of sleep due to the fact that the real response of excitation of motility is replaced by hallucinatory excitation, which does not require awakening. On the other hand, dreaming allows repressed desires, albeit in a distorted form to fulfil and thus reduce the mental stress associated with sexual or aggressive impulses. Thus the dream is designed to reconcile two opposing forces - the desire to sleep and the desire to act in accordance with the excitement emanating from the mental or somatic sphere. The emotional daytime experience takes precedence over other less emotional experiences, during inclusion in dreams because emotions provide an automatic and unconscious way of determining which experiences to include in a dream for memorization. Dreams can be a representation of the real and the repressed desires, but the emotional component of sleep is important as it may indicate the presence of traumatic experiences. The hidden meaning of dreams becomes clear to the participants’ analytical process through the use of the method of free associations, as well as through emphasis on the manifesto of dreams. Unconscious communication between the patient and the analyst is well reflected in the meaning of sleep. Conclusions. Analysis of the content of dreams can provide important information about the mental state of the individual and contribute to a better understanding of the patient and analytical processes. Working with dreams is an important part of the analytical process, a symbolic reflection of the inner world of the patient, the analyst, the unconscious third and the processes that occur in therapy. Dreams represent hidden desires and emotional and/or traumatic experiences of a particular patient.